Aktivitas Antibakteri Emulgel dan Uji Sifat Fisik Ekstrak Etanol Daun Sumambu terhadap Escherichia coli FNCC 0091 - Maulana Tegar Adityanugraha; Ferli Eko Kurniantoro; Raodatul Fitri (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
Sumambu leaves (Hyptis capitata Jacq.) can be utilized as a traditional medicinal remedy. However, the direct application of sumambu leaves on the skin is impractical and uncomfortable, so they are formulated into an emulgel dosage form. This study aims to evaluate the physical properties and antibacterial activity of sumambu leaves. This research is an experimental study. The test material was sumambu leaf powder, which was extracted using the maceration method with 96% ethanol as the solvent. The concentrated extract was then formulated into an emulgel and tested for its physical properties, including organoleptic characteristics, spreadability, adhesiveness, and pH. Antibacterial activity against Escherichia coli was tested using the well diffusion method. The antibacterial activity was indicated by the presence of inhibition zones in emulgels with concentrations of 5%, 10%, and 15%. The analysis used in this study was descriptive analysis. The results of the physical property tests showed that the emulgel of sumambu extract had good organoleptic properties, adhesiveness, and pH. However, its spreadability did not meet the standard criteria, as the required spread diameter for a good emulgel preparation is 5–7 cm. The antibacterial activity test results showed that the emulgel of sumambu leaf extract exhibited antibacterial activity against Escherichia coli at concentrations of 5%, 10%, and 15%, with average inhibition zone values of 18 mm, 22 mm, and 26 mm, respectively. These results indicate that the emulgel of sumambu leaf extract possesses antibacterial activity against Escherichia coli FNCC0091.